2003
DOI: 10.1590/s0006-87052003000100009
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e mortalidade larval de Spodoptera frugiperda em folhas de milho tratadas com extrato aquoso de folhas de Azadirachta indica

Abstract: Estudou-se o efeito do extrato aquoso de folhas de nim sobre o desenvolvimento e a mortalidade de lagartas recém-eclodidas de Spodoptera frugiperda. Para constatação do efeito de contato e de ingestão, as lagartas foram pulverizadas e as folhas de milho submersas no extrato (10 mg.mL-1) em laboratório e/ou pulverizadas no campo com um pulverizador de CO2. Partes de folhas de milho tratadas foram colocadas em copos plásticos para alimentar as lagartas e trocadas a cada dois dias. Adjuvantes foram adicionados ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
2
16
0
8
Order By: Relevance
“…This might be because their seeds are very oily, originating an equally oily extract and this oil could act as an adjuvant, improving the fixation and distribution of the S. saponaria aqueous extract in the maize leaves offered as food for the caterpillars, promoting an increase in the insecticide action. Viana and Prates (2003) observed the same results in a field study, where they tested aqueous extracts (10% w/v) of A. indica leaves, with and without the addition of soy oil, against S. frugiperda caterpillars and the mortality was 45.6% for the aqueous extract A. indica and 71.7% for the aqueous extract A. indica + soy oil. In the anti-trypsin assays the results showed that the aqueous extract of T. esculenta did not inhibit the activity of the bovine trypsin enzyme.…”
Section: Discussionsupporting
confidence: 58%
“…This might be because their seeds are very oily, originating an equally oily extract and this oil could act as an adjuvant, improving the fixation and distribution of the S. saponaria aqueous extract in the maize leaves offered as food for the caterpillars, promoting an increase in the insecticide action. Viana and Prates (2003) observed the same results in a field study, where they tested aqueous extracts (10% w/v) of A. indica leaves, with and without the addition of soy oil, against S. frugiperda caterpillars and the mortality was 45.6% for the aqueous extract A. indica and 71.7% for the aqueous extract A. indica + soy oil. In the anti-trypsin assays the results showed that the aqueous extract of T. esculenta did not inhibit the activity of the bovine trypsin enzyme.…”
Section: Discussionsupporting
confidence: 58%
“…For the preparation of aqueous extract, neem leave dust was soaked in distilled water for 24 h at room temperature at dark as described by Viana and Prates (2003). The preparations of different concentrations were filtered and stored in amber glass bottles at 4°C.…”
Section: Preparation Of Aqueous Extract From Neem Leaf Dustmentioning
confidence: 99%
“…To control S. frugiperda, the efficiency of leaf extract and branches of Trichilia pallida Sw (Meliaceae) in ethyl acetate (ROEL et al, 2000) and aqueous extract of leaves of nim (Azadirachta (SOUZA et al, 2010;ZHANG et al, 2014), of some species of the genus Piper spp. (SCOTT et al, 2008) and Lippia alba (Mill.)…”
Section: Introductionmentioning
confidence: 99%